Consumer Protection of Travel Package Service Users (Comparative Study of Indonesia and Sweden) - Kadek Nadya Pramita Sari (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2022)
There are differences in consumer protection arrangements in Indonesia and Sweden, especially in consumer protection for travel package service users. Indonesia does not have special arrangements to protect consumers using travel package services, while Sweden regulates it specifically through the Package Travel Act. This study aims to analyze the comparison of consumer protection arrangements in Indonesia and Sweden which specifically seeks to analyze the application of the Consumer Protection Act in the event of a violation of consumer rights in the relationship between buying and selling travel package services between business actors and consumers. The research used normative legal research by applying a statute approach and a comparative approach. This research is descriptive, and data is obtained from secondary data or library research. The results of this study on comparisons related to consumer protection arrangements in Indonesia and Sweden are different in terms of the scope of the regulation where Indonesia in the Consumer Protection Law regulates consumer protection in general or not fundamentally on the type of goods or services while Sweden regulates protection according to the type of goods. or services. Regarding the implementation of the Consumer Protection Law in Didit Wijayanto and Traveloka cases in the Bogor District Court Decision No. 123/Pdt.G/2019/PN Bgr in its implementation cannot protect consumer rights to convenience and immaterial interests, namely losses outside of finance. Then against the settlement of the Didit Wijayanto and Traveloka cases based on the Package Travel Act of Swedish there is a strict provision that states that for technical errors in the booking system that cause losses, consumers are entitled to compensation either financial or non-financial compensation.